Tick saliva is a potent inhibitor of endothelial cell proliferation and angiogenesis - Francischetti, Ivo M B; Mather, Thomas N; Ribeiro, José M C (Thrombosis and haemostasis, 2005)
We report for the first time that saliva of the hard tick and Lyme disease vector, Ixodes scapularis, is a potent inhibitor of angiogenesis. Saliva (< or = 1:500 dilutions) or salivary gland (0.1-0.5 pairs/assay) dose-dependently inhibits microvascular endothelial cell (MVEC) proliferation. Inhibition was also detected with the saliva of the cattle tick Boophilus microplus but not with the salivary gland of Anopheles gambiae, An. stephensi, Lutzomyia longipalpis, Phlebotomus papatasi, Aedes aegypti, Culex quinquefasciatus, and Cimex lectularius. Inhibition of MVEC proliferation by I. Scapularis saliva was accompanied by a change in cell shape (shrinkage of the cytoplasm with loss of cell-cell interactions) and apoptosis which was estimated by expression of phosphatidylserine using the Apopercentage dye, and by a typical pattern of chromatin margination, condensation, and fragmentation as revealed by nuclear staining with Hoechst 33258. The effect of saliva appears to be mediated by endothelial cell alpha5beta1 integrin, because monoclonal antibodies against this but not alphavbeta3, alphavbeta5, alpha9beta1, or alpha2beta1 integrins remarkably block its effect. In addition, SDS/PAGE shows that saliva specifically degrades purified alpha5beta1 but not alphavbeta5 or alphavbeta3 integrins. Incubation of saliva with EDTA and 1,10-phenanthroline, but not phenylmethylsulfonyl fluoride (PMSF), inhibits saliva-dependent degradation of purified alpha5beta1 integrin, suggesting that a metalloprotease is responsible for the activity. Finally, saliva at < or = 1:1,000 dilutions blocks sprouting formation from chick embryo aorta implanted in Matrigel, an in vitro model of angiogenesis. These findings introduce the concept that tick saliva is a negative modulator of angiogenesis-dependent wound healing and tissue repair, therefore allowing ticks to feed for days. Inhibition of angiogenesis was hitherto an unidentified biologic property of the saliva of any blood-sucking arthropod studied so far. Its presence in tick saliva may be regarded as an additional source of angiogenesis inhibitors with potential applications for the study of both vector and vascular biology.